ADVANCED MATHEMATICAL TECHNIQUES IN COMPUTATIONAL AND INTELLIGENT SYSTEMS - Singh, Sandeep; Haghighi, Aliakbar Montazer; Dalal, Sandeep (CRC PRESS, 2023)
This book comprehensively discusses the modeling of real-world industrial problems and innovative optimization techniques such as heuristics, finite methods, operation research techniques, intelligent algorithms, and agent- based methods. Discusses advanced techniques such as key cell, Mobius inversion, and zero suffix techniques to find initial feasible solutions to optimization problems. Provides a useful guide toward the development of a sustainable model for disaster management. Presents optimized hybrid block method techniques to solve mathematical problems existing in the industries. Covers mathematical techniques such as Laplace transformation, stochastic process, and differential techniques related to reliability theory. Highlights application on smart agriculture, smart healthcare, techniques for disaster management, and smart manufacturing. Advanced Mathematical Techniques in Computational and Intelligent Systems is primarily written for graduate and senior undergraduate students, as well as academic researchers in electrical engineering, electronics and communications engineering, computer engineering, and mathematics.
Keywords: Computational intelligence; Artificial intelligence -- Mathematics; Mathematical optimization; Intelligence informatique; Intelligence artificielle; Mathématiques; Optimisation mathématique; TECHNOLOGY / Electricity; TECHNOLOGY / Operations Research; COMPUTERS / Computer Engineering; Artificial intelligence; Mathematics